Log-periodogram estimation of the memory parameter of a long-memory process under trend - Philipp Sibbertsen (Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2001)
We show that small trends do not influence log-periodogram based estimators for the memory parameter in a stationary invertible long-memory process. In the case of slowly decaying trends which are easily confused with long-range dependence we show by Monte Carlo methods that the tapered periodogram is quite robust against these trends and thus provides a good alternative to standard logperiodogram methodology.
Keywords: C14; C22; 519; Long-memory; trends; log-periodogram regression